Olah Limbah Jadi Pupuk: Pendampingan Siswa SDN Tingkir Lor Satu Kota Salatiga dalam Mengolah Air Limbah Tempe menjadi Produk Bernilai Guna - Widhi Handayani (Universitas Negeri Makassar, 2026)
The existence of various environmental problems requires the community not only to address this situation, but also to take action to prevent environmental damage. Environmental education is an effort that can be done to build environmental awareness in elementary school students from an early age, so that they can become agents of change in Indonesia towards environmental sustainability. Tingkir Lor 01 Public Elementary School, Salatiga, is in the process of becoming an Adiwiyata school under the guidance of Salatiga 2 Public Senior High School and carries out various programs, one of which is training to address environmental problems in the surrounding area. Therefore, this community service activity was carried out to provide training for students and teachers of Tingkir Lor 01 Public Elementary School, Salatiga in making liquid fertilizer from tempeh wastewater as an alternative to convert materials considered useless into useful products. The activity was carried out using the experiential learning method so that students can gain direct experience during the learning process. This activity has been carried out, and students and teachers can participate well in this activity. Although the material provided is still too complex for elementary school students in grades IV and V, the material provided is understandable by the teacher and students can gain learning experience through the practice of making liquid fertilizer.